2018
DOI: 10.1038/s41386-018-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment and early-treatment cortical thickness is associated with SSRI treatment response in major depressive disorder

Abstract: To date, there are no biomarkers for major depressive disorder (MDD) treatment response in clinical use. Such biomarkers could allow for individualized treatment selection, reducing time spent on ineffective treatments and the burden of MDD. In search of such a biomarker, multisite pretreatment and early-treatment (1 week into treatment) structural magnetic resonance (MR) images were acquired from 184 patients with MDD randomized to an 8-week trial of the selective serotonin reuptake inhibitor (SSRI) sertralin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 62 publications
3
55
2
1
Order By: Relevance
“…Within weeks after administration of the cytokine IFN-a, patients experience symptoms (Capuron et al, 2002;Capuron and Miller, 2004) due to dopamine loss (Capuron et al, 2012). Similar results were reported in animal studies (Felger et al, 2007(Felger et al, , 2013 in which lipopolysaccharide or cytokine administration (IL-1b or IL-6) in mice resulted in loss of interest and reduction in reward sensitivity (Yohn et al, 2016;Bartlett et al, 2018). Another essential cofactor in monoamine synthesis, tetrahydrobiopterin, decreases in response to inflammation-induced oxidative stress (ROS and reactive nitrogen species), inducing anxiety and depressive symptoms (Neurauter et al, 2008;Haroon et al, 2012;Felger et al, 2013).…”
Section: Inflammatory Effects On Neurotransmitter Metabolismsupporting
confidence: 67%
“…Within weeks after administration of the cytokine IFN-a, patients experience symptoms (Capuron et al, 2002;Capuron and Miller, 2004) due to dopamine loss (Capuron et al, 2012). Similar results were reported in animal studies (Felger et al, 2007(Felger et al, , 2013 in which lipopolysaccharide or cytokine administration (IL-1b or IL-6) in mice resulted in loss of interest and reduction in reward sensitivity (Yohn et al, 2016;Bartlett et al, 2018). Another essential cofactor in monoamine synthesis, tetrahydrobiopterin, decreases in response to inflammation-induced oxidative stress (ROS and reactive nitrogen species), inducing anxiety and depressive symptoms (Neurauter et al, 2008;Haroon et al, 2012;Felger et al, 2013).…”
Section: Inflammatory Effects On Neurotransmitter Metabolismsupporting
confidence: 67%
“…61 Moreover, an early increase in hippocampal volume and in rostral anterior cingulate thickness after 1 week of treatment was predictive of improved clinical response to antidepressant treatment with serotonin and noradrenaline reuptake inhibitor antidepressant drugs, suggesting that neuroplastic cellular changes may occur early and are predictive of subsequent clinical efficacy. 62,63 Furthermore, decreased hippocampal gray matter in MDD in a current depressive episode, relative to healthy participants and MDD in remission, subsequently showed increased gray matter after SSRI antidepressant treatment, 61 perhaps representing a human in vivo correlate of cellular neurogenesis with SSRI pharmacologic treatment in animal models. 64 MR imaging observable changes in hippocampal structure, as well as in other cortical and subcortical regions, reflect the complex inter-relationships of neurotoxic and neuroplastic cellular effects.…”
Section: Systems and Neuroplasticitymentioning
confidence: 99%
“…A multivariate pattern analysis using the gray matter and white matter magnetic resonance image at baseline differentiated treatment-sensitive patients from treatment-resistant patients with 82.9% accuracy [34]. A large, multisite, and placebo-controlled MRI study examined the association between the efficacy of sertraline and the cortical thickness at baseline and after 1 week [35]. It was found that increased cortical thickness of the rostral anterior cingulate cortex after 1 week of treatment was associated with better response to selective serotonin reuptake inhibitors (SSRI) at 8 weeks; however, the predictive accuracy (63.9%) in differentiating treatment response from nonresponse was relatively limited [35].…”
Section: Structural Imaging and Volumetric Datamentioning
confidence: 99%
“…A large, multisite, and placebo-controlled MRI study examined the association between the efficacy of sertraline and the cortical thickness at baseline and after 1 week [35]. It was found that increased cortical thickness of the rostral anterior cingulate cortex after 1 week of treatment was associated with better response to selective serotonin reuptake inhibitors (SSRI) at 8 weeks; however, the predictive accuracy (63.9%) in differentiating treatment response from nonresponse was relatively limited [35]. The structural MRI results of 53 unipolar depressed patients showed that a larger amygdala volume was significantly associated with a lower post-electroconvulsive therapy (ECT) Montgomery-Asberg Depression Rating Scale score.…”
Section: Structural Imaging and Volumetric Datamentioning
confidence: 99%